Role of EIF4G1 network in non‐small cell lung cancers (NSCLC) cell survival and disease progression. Issue 6 (4th February 2021) - Del Valle, Luis; Dai, Lu; Lin, Hui‐Yi; Lin, Zhen; Chen, Jungang; Post, Steven R.; Qin, Zhiqiang
Abstract: Although the Eukaryotic Translation Initiation Factor 4 Gamma 1 (EIF4G1) has been found overexpressed in a variety of cancers, its role in non–small cell lung cancers (NSCLC) pathogenesis especially in immunoregulatory functions, its clinical relevance and therapeutic potential remain largely unknown. By using cancer patients tissue assays, the results indicate that EIF4G1 expressional levels are much higher in NSCLC tissues than in adjacent or normal lung tissues, which are also associated with NSCLC patient survival. By using an RNA‐Sequencing based pipeline, the data show that EIF4G1 has a significant association with immune checkpoint molecules such as PD‐1/PD‐L1 in NSCLC. EIF4G1 small‐molecule inhibitors effectively repress NSCLC growth in cell culture and xenograft animal models. Protein array results identify the signature of proteins controlled by EIF4G1 in NSCLC cells, in which new candidates such as MUC1 and NRG1 are required for NSCLC survival and tumorigenesis with clinical relevance. Taken together, these results have for the first time demonstrated the immunoregulatory functions, clinical relevance and therapeutic potential of the EIF4G1 network in NSCLC, which may represent a promising and novel target to improve lung cancer treatment.